Revitalization of Fisherman and Rural Economy For Acceleration of Poverty Reduction In The Digital Era: Roots of Problems and Solutions - Andi Cahaya (Jurnal Ad'ministrare, 2022)
The results of this normative research article are the contents of the inaugural speech by Professor Dr. Dra. Andi Cahaya, M.Sc., who discussed "repositioning" or revitalizing the fishermen and rural economies to accelerate poverty reduction in the digital era. The revitalization of the fishermen's economy as the focus of the blue revolution program locus is a zine-qua-non promoted by the current government to accompany the successful green revolution program. Fishermen poverty is a multi-dimensional problem that requires a comprehensive solution. The type of normative research or literature study is used to collect data, information, and knowledge about the focus of the research locus to be analyzed descriptively. The results of the study found that the causes of poverty are not the same in all regions, even if the size or scale varies depending on local conditions so poverty alleviation strategies cannot be generalized to all regions or all sectors. The poverty experienced by rural fishermen cannot be equated with the measure of poverty in urban communities. Therefore, fishermen and rural poverty alleviation programs require a revitalization strategy through increasing skills and mastery of information and communication technology (ICT) for actors to be able to improve the quality of their business. In addition, simultaneous cultural and structural revitalization is needed to provide a way to alleviate fishermen and rural poverty in the context of achieving the Millennium Development Goals (MDGs) proclaimed by the Indonesian government.